2001
DOI: 10.1016/s0022-5347(01)69897-5
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of the Virulence Island Containing the Usp Gene in Uropathogenic Escherichia Coli Is Associated With Urinary Tract Infection in an Experimental Mouse Model

Abstract: Our results indicate that usp may contribute to the causation of urinary tract infection and may be considered a major virulence determinant of uropathogenic E. coli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 19 publications
2
36
0
Order By: Relevance
“…In a series of studies, we reported usp as a new urovirulence factor that was more frequently found in UPEC strains associated with different symptoms in humans (3). Using a pyelonephritis mouse model, we also demonstrated that the presence of the virulence island containing usp in UPEC was associated with infection (9).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In a series of studies, we reported usp as a new urovirulence factor that was more frequently found in UPEC strains associated with different symptoms in humans (3). Using a pyelonephritis mouse model, we also demonstrated that the presence of the virulence island containing usp in UPEC was associated with infection (9).…”
Section: Discussionmentioning
confidence: 74%
“…The PI contains usp that encodes a 346-amino acid protein, which we designated as uropathogenic specific protein (Usp), and three small open reading frames (orfU1-3). Further, we demonstrated that Usp significantly enhanced the infectivity of E. coli whereas the three small proteins downstream of usp failed to exhibit this effect in mouse urinary tract infection model (9). The structural and sequence diversity of the PI of UPEC which encodes the Usp protein 798 H. KURAZONO ET AL Fig.…”
mentioning
confidence: 87%
“…Recently, a new urovirulence factor gene, which was more frequently found in UPEC strains, was reported. This gene encoding a protein designated usp (uropathogenic-specific protein) was demonstrated significantly enhancing the infectivity of E. coli in the mouse UTI model 15,18,28 .…”
Section: Introductionmentioning
confidence: 99%
“…E. coli strain Z42 was isolated from a patient suffering from an inflammation of the prostate gland (prostatitis). The DNA element carrying the usp gene was found on the chromosome of a large number of UPEC strains (4) and is significantly more frequently associated with UPEC strains than with faecal E. coli strains from healthy individuals (8). In addition, the contribution to virulence of the Usp protein in uropathogenic E. coli was assessed using an experimental mouse model.…”
Section: Christopher M Thomas Editor-in-chiefmentioning
confidence: 99%